Influence of Guided Discovery Learning Strategy on Motivation and Learning Outcomes on Natural Science of Students in Class IV Rantepao I SDN Toraja Utara - Benyamin Salu (Pascasarjana Universitas Negeri Malang (UM), 2013)
Pengaruh Strategi Penemuan Terbimbing terhadap Motivasi dan Hasil Belajar IPA Siswa Kelas IV SDN Rantepao I Kabupaten Toraja UtaraAbstract: The study aims to determine: 1) the influence of guided discovery learning strategy in science subjects on motivation to learn and 2) the effect of guided discovery learning strategy in science subjects on learning outcomes. The study design is experimental design. The subjects were students of class IV SDN Rantepao I of Toraja Utara consisting of two classes with 38 students in a class IVA and 37 students in class IVB. The Data collection technique used observation, questionnaires, and tests. The Hypothesis testing is using Anacova Techniques. The results shows that motivation and student learning outcomes is higher in guided discovery learning strategy compared to the conventional strategy. Key Words: strategy guided discovery, learning motivation, learning outcomes Abstrak: Penelitian bertujuan mengetahui: 1) pengaruh strategi penemuan terbimbing pada mata pelajaran IPA terhadap motivasi belajar dan 2) pengaruh strategi penemuan terbimbing pada mata pelajaran IPA terhadap hasil belajar. Rancangan penelitian adalah desain eksperimen. Subjek penelitian adalah siswa kelas IV SDN Rantepao I Kabupaten Toraja Utara yang terdiri dari dua kelas yaitu kelas IVA 38 siswa dan IVB 37 siswa. Teknik pengumpulan data menggunakan observasi, angket, dan tes. Pengujian hipotesis menggunakan teknik Anacova. Hasil penelitian menunjukkan bahwa motivasi dan hasil belajar siswa lebih tinggi pada strategi penemuan terbimbing dibanding strategi konvensional.Kata kunci: strategi penemuan terbimbing, motivasi belajar, hasil belajar